External respiration system adaptation in finswimming - Dyakova, E. Yu.; Mironov, A. A. (Theory and Practice of Physical Culture, 2019)
The growing competitiveness in the finswimming sport urges the sport community look for the ways to improve the elite training systems to secure competitive progress. In the educational domain, the long-term training systems give a due priority to the swimming techniques and tactics albeit the biomedical aspects of the training systems remain still underdeveloped. The study analyzes the external respiration system adaptation mechanisms in the modern finswimming sport. Sampled for the study were the 18-23 year old elite underwater finswimmers, surface swimmers (with the 9+ year sport records) and students split up into the following three groups: Experimental Group (EG, n=15) of underwater finswimmers; Reference Group 1 (RG1, n=15) of the surface swimmers and RG2 (n=15) of the Tomsk State University students trained in the traditional body conditioning groups. The EG and RG1 were trained 1-2 times per day 5-6 times a week; and the RG2 was trained 2-3 times a week. Spirometric test data were mined by the Valenta Computerized Test System made by Neo Company, Russia. The external respiration test data were found significantly different for the above groups, with the finswimmers adaptation growth rates found significantly better than that in the RG1 and RG2. The progress may be attributed to the hypoxic training effects of the modern finswimming training system.